MODEL OF DIGITAL FIBER-OPTIC SYSTEM FOR MEASURING OBJECT SIZES - Окоча, С. В. (Science-based technologies, 2013)
In this study a new approach to get a generalized mathematical model of digital fiber-distributed interferometer measuring system has been proposed. By using this approach generalized equations of conversion for digital fiber-optic converters of measured object’s geometrical coordinates have been obtained, joining all private mathematical models of information processes which occur in analogue, analogue-digital and digital structural blocks while working under static and dynamic conditions. In general, the essence of the proposed approach is based on representation of characteristics of the "coordinate point- code" presented in the form of the equation of an ideal digital-to-analog conversion of the source code, the processes of bit code change given in the form of logical functions of input points and movement of actual multi-dimensional parameter measuring path.